FSO Receiver With Adaptive Alignment Based on Pure Phased Holographic Imaging - Wang, Haibo; Zhang, Zaichen; Zhang, Yidi (Frontiers in Physics, 2021)
This paper proposes a free space optical communication (FSO) receivier system with adaptive alignment based on pure phase holographic imaging. During the frame header transmission period, the optical phased array in this system performs specific holographic imaging on the receiving plane, which assist the system to undergo beam alignment. The system model has been built in this work, along with the receiving signal expression. Based on the physical model, we propose an algorithm for positioning calibration and the circuitous phased encoding for improvement of imaging quality and algorithm complexity.